Fields of Logic and Computation: Essays Dedicated to Yuri Gurevich on the Occasion of His 70th Birthday - Blass, Andreas; Dershowitz, Nachum; Reisig, Wolfgang (Lecture Notes in Computer Science, 2010)
This Festschrift volume, published in honor of Yuri Gurevich on the occasion of his 70th birthday, contains contributions written by his colleagues. The articles cover a range of topics - representing only a fraction of Gurevich's multiple areas of interest.